2013
DOI: 10.1002/adma.201204616
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin PEGylated W18O49 Nanowires as a New 980 nm‐Laser‐Driven Photothermal Agent for Efficient Ablation of Cancer Cells In Vivo

Abstract: A new photothermal coupling agent for photothermal ablation (PTA) therapy of tumors is developed based on ultrathin PEGylated W18O49 nanowires. After being injected with the nanowire solution, the in vivo tumors exhibit a rapid temperature rise to 50.0 ± 0.5 °C upon irradiation with NIR laser light at a safe, low intensity (0.72 W cm(-2)) for 2 min (left-hand mouse in the figure),), resulting in the efficient PTA of cancer cells in vivo in 10 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
264
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 375 publications
(268 citation statements)
references
References 45 publications
3
264
0
1
Order By: Relevance
“…[ 8,11 ] Photothermal therapy (PTT) usually employs near-infrared (NIR) light-absorbing agents to generate heat from optical energy, leading to thermal ablation of cancer cells. [ 12 ] In the past decade, a large number of NIR-absorbing nanomaterials, such as different gold nanostructures, [ 13 ] carbon-based nanomaterials, [ 12,14 ] palladium nanosheets, [ 15 ] copper sulfi de nanoparticles, [ 16 ] tungsten oxide nanowires, [ 17 ] as well as various organic polymers and nanoparticles, [ 18 ] have been widely explored by many research groups including ours as photothermal agents for PTT ablation of cancer in vitro and in vivo. In a recent work, Chou et al for the fi rst time demonstrated the possibility of using as-made MoS 2 nanosheets as a new NIR absorbing agent for in vitro-photothermal-killing of cancer cells in vitro at the cell culture level.…”
Section: Doi: 101002/adma201304497mentioning
confidence: 99%
“…[ 8,11 ] Photothermal therapy (PTT) usually employs near-infrared (NIR) light-absorbing agents to generate heat from optical energy, leading to thermal ablation of cancer cells. [ 12 ] In the past decade, a large number of NIR-absorbing nanomaterials, such as different gold nanostructures, [ 13 ] carbon-based nanomaterials, [ 12,14 ] palladium nanosheets, [ 15 ] copper sulfi de nanoparticles, [ 16 ] tungsten oxide nanowires, [ 17 ] as well as various organic polymers and nanoparticles, [ 18 ] have been widely explored by many research groups including ours as photothermal agents for PTT ablation of cancer in vitro and in vivo. In a recent work, Chou et al for the fi rst time demonstrated the possibility of using as-made MoS 2 nanosheets as a new NIR absorbing agent for in vitro-photothermal-killing of cancer cells in vitro at the cell culture level.…”
Section: Doi: 101002/adma201304497mentioning
confidence: 99%
“…[57][58][59][60] Chen et al 58 and other groups reported the preparation of ultrathin PEGylated W 18 O 49 nanowires through a solvothermal reaction of a WCl 6 precursor in a mixture of PEG (M w = 400 Da) and ethanol solutions. A 980 nm wavelength laser was used to instantly convert photoenergy into thermal energy at a safe power density (0.72 W cm − 2 ).…”
Section: Chalcogenide-based Nanomaterialsmentioning
confidence: 99%
“…• C within 400 s by irradiation with a 980 nm laser (0.72 W/cm 2 ), which probably efficiently induces cancer cells death [29].…”
Section: Resultsmentioning
confidence: 99%